An Ovarian Cancer Patient Presenting Heparin - Induced Thrombocytopenia after use of Low - Molecular - Weight Heparin: A Case Report of Rare Condition - Durmuş, Yasin; Karyal, Yalin Ay; Kilic, Cigdem; Cakir, Caner; Yuksel, Dilek; Seyhan, Berna; Boyraz, Gokhan; Kimyon Comert, Gunsu; Turan, Taner (Gynecology Obstetrics & Reproductive Medicine, 2019)
Heparin-induced thrombocytopenia is a rare and life-threatening condition of exposure to heparin. A case of heparin-induced thrombocytopenia due to the low molecular weight heparin was presented. Pulmonary emboli and progressively decreased number of thrombocytes developed during the low molecular weight heparin treatment. For that reason, the heparin-induced thrombocytopenia was diagnosed. The heparin was ceased and fondaparinux treatment initiated. Platelet levels returned to normal limits within six days. The delaying in diagnosis of heparin-induced thrombocytopenia causes serious outcomes. The physician must be careful and keep in mind be developed of this clinical condition in patient under heparin treatment.